Hubungan Ketepatan Peresepan Obat Anti Hipertensi Terhadap Tekanan Darah Pasien Hipertensi - Magdalena Yosefin Saputra; dyah wulan sumekar rw; rasmi zakiah oktarlina (CV. Jasa Sukses Abadi, 2023)
Hypertension is a disease characterized by an increase in a person's blood pressure more than the normal blood pressure threshold. Hypertension is the 3rd most common cause of premature death in the world. This disease is also called the silent killer because most sufferers do not experience specific complaints, but complaints arise after organ abnormalities due to hypertension. Efforts to prevent and treat hypertension can be started with lifestyle changes such as consumption of fruits and vegetables, low consumption of salt and fat, regular exercise, and not smoking. Furthermore, treatment in the form of pharmacological management is also needed to regulate blood pressure so that it does not exceed normal limits. Administration of anti-hypertensive drugs also aims to prevent complications due to high blood pressure. Pharmacological treatment uses antihypertensive drugs such as diuretics, andrenergic blockers, angiotensin converting enzyme inhibitors (ACE-inhibitors), angiotensin-II inhibitors, calcium antagonists, direct vasodilators. Achieving the target of therapy in hypertensive patients means that there is a decrease in blood pressure until it reaches normal limits. In patients who receive antihypertensive drug prescriptions correctly, it is assessed that they have a 6 to 13-fold possibility of getting antihypertensive therapeutic effects that are on target compared to patients who receive antihypertensive drug therapy not right.